Protocol for a qualitative mechanistic study of MDMA with a sample of psychoanalytic psychotherapists: A phenomenological investigation - Elisa Liberati; H. Valerie Curran; Peter Fonagy; Henry Clements; Alessandra Lemma; Rosalind McAlpine; David J. Nutt; Anne Katrin Schlag; Sunjeev K. Kamboj (PLoS ONE, 2026)
Introduction Methylenedioxymethamphetamine (MDMA)-assisted psychotherapy (MDMA-AP) is a potentially transformative intervention for post-traumatic stress disorder (PTSD). Despite encouraging Phase III trial results, the psychological mechanisms underpinning MDMA’s therapeutic effects remain insufficiently understood. Existing research on MDMA has emphasised neurobiological processes but has not adequately incorporated subjective, relational, and experiential processes that are likely to be central to optimising psychedelic-assisted treatments. In the absence of an established clinical psychological theory of MDMA-AP, qualitative approaches can support theory development to refine and optimise MDMA-AP, and identify cross-diagnostic change processes that may broaden its therapeutic scope. Materials and methods Approximately 25 experienced psychodynamically trained psychotherapists will receive two doses of MDMA (80–120 mg, oral), separated by ≥1 week, under controlled research conditions in an open-label, qualitative mechanistic study. Clinician-participants will complete baseline interviews examining beliefs and attitudes toward MDMA-AP, brief phenomenological interviews during MDMA sessions, in-depth phenomenological and theory-oriented follow-up interviews examining experience and understandings of MDMA-associated change processes, and daily reflective journals between dosing sessions. Additional standardised measures will assess reflective functioning and related constructs. Qualitative data will be analysed using phenomenological and thematic approaches, and grounded theory-inspired techniques will be used to develop a theoretically coherent model of MDMA’s psychological mechanisms of action grounded in the full dataset. Discussion In this study of MDMA’s potential mechanisms-of-action, we treat psychotherapists as expert observers of their own psychological processes. By examining first-hand experience in participants selected for their well-developed capacity for self-reflection, meta-awareness, and advanced theoretical and clinical frameworks for understanding mental phenomena, psychopathology, and psychological treatment, we anticipate generating novel insights into MDMA’s therapeutic mechanisms-of-action. The primary study output will be a theoretically grounded model of MDMA’s psychological mechanisms of action, intended to inform novel treatment models amenable to future experimental evaluation. The study also offers a transferable framework for qualitative mechanistic investigations of psychedelic compounds, supporting the development of integrative and evidence-based models of psychedelic therapy.